Odpowiedzi

2009-12-06T18:46:10+01:00
Witaj:)
x=0,15*⅚-(0,7*³/₇ - ⁴/₅) :(1½)
x= 15/100*5/6 - ( 7/10*3/7 -4/5) : 3/2
x= 1/8 - (3/10 - 4/5) :3/2
x= 1/8 - (3/10 - 8/10) :3/2
x= 1/8 - ( -5/10) * 2/3
x= 1/8 - ( -1/2) * 2/3
x= 1/8 + 1/3
x= 3/24+8/24
x= 11/24

2009-12-06T18:51:34+01:00
X=15/100*5/6-(7/10*3/7-4/5)/(3/2)
x=1/8-(3/10-8/10)*(2/3)
x=1/8-(-1/2)*(2/3)
x=1/8-(-1/3)
x=1/8+1/3
x=3/24+8/24
x=11/24
2009-12-06T18:51:35+01:00
X=0,15*⅚-(0,7*³/₇ - ⁴/₅) :(1½)
x=15/100*⅚-(7/10*³/₇- ⁴/₅)×(2/3)
x=1/8-(3/10-8/10)×(2/3)
x=1/8-(-5/10)×(2/3)
x=1/8-(-1/2)×(2/3)
x=1/8+1/3
x=3/24+8/24
x=11/24